The interplay of competitive and cooperative behavior and differential benefits in alliances - Arslan, Birgul (Strategic Management Journal, 2017)
Research Summary : Building on game theory and the transaction costs paradigm, this paper systematically examines the interplay between competitive and cooperative behavior and its effect on differential benefits in alliances. Cooperative behavior leads to joint value creation that yields common benefits, while competitive behavior is linked with value appropriation resulting in private benefits. Differential benefits arise when partners extract private benefits. Yet, private benefit extraction depends on the associated reduction in the common benefit potential of the alliance. This paper demonstrates that differential benefits decrease as partners refrain from private benefit extraction when the common benefit potential is high and common benefits are equally distributed. Differential benefits increase when a partner holds dominant operational control under high levels of task interdependence. Managerial Summary : While alliances create synergy potential unavailable to individual firms, they may also lead to differential benefits to the partners. Since differential benefits may hurt a partner both within and outside the scope of the alliance, it is important to understand how they arise. A key source of differential benefits is private benefit extraction through the misappropriation of partner resources. Overall, private benefit extraction depends on the associated reduction in the common benefit potential of the alliance. The findings suggest that partners may refrain from private benefit extraction when the common benefit potential is high and when the expected common benefits are equally distributed among partners. In contrast, private benefits increase when one partner holds dominant operational control under high levels of task interdependence.